A IOT-Based Safety Helmet for Monitoring Carbon Monoxide Levels in Mining - Bayhaqi, Iulyvia Andhani; Aksan, Muhammad Dhafi Aksan (Indonesian Journal of Electrical Engineering and Electronics, 2025)
This research discusses the development of an Internet of Things (IoT)-based safety helmet designed to monitor carbon monoxide (CO) levels in high-risk areas, such as mining. The helmet is equipped with an MQ-7 sensor that detects CO concentration and provides alerts through a buzzer and notifications to the Blynk app when CO levels exceed 35 ppm. The test results show that the helmet can detect CO levels in real-time with good accuracy. During testing, the CO levels remained below 35 ppm until 01:15, but increased to 36.21 ppm at 01:40, triggering the buzzer and a "Danger" notification. This system proves reliable as a hazardous gas monitoring tool and can enhance workplace safety in high-risk areas like mining by providing early warnings of potential gas poisoning hazards.